Symptomatic cervical disc herniation in teenagers: two case reports - Abe, Toshiki (BioMed Central, 2013)
INTRODUCTION: The development of a symptomatic herniated cervical disc before the age of 20 is extremely rare. Sporadically reported cases of patients with cervical disc herniation under the age of 20 usually have had underlying disease. CASE PRESENTATION: Case 1: A 19-year-old Asian man visited our clinic and presented with progressive pain in his upper left scapula and weakness of the left deltoid and biceps brachii muscles. C5 radiculopathy by soft disc herniation at C4-C5 without calcification was diagnosed. Microsurgical posterior foraminotomy was performed and he recovered completely eight weeks after the surgery. Case 2: A 15-year-old Asian man presented with difficulty in lifting his arm and neck pain on the right side. Neurological examination showed weakness of the right deltoid and biceps brachii muscles. A magnetic resonance imaging scan demonstrated a herniated intervertebral disc in the right C4-C5 foramen. The patient was treated conservatively and put under observation only, and had completely recovered eight weeks after admission. CONCLUSION: Although extremely rare, symptomatic cervical disc herniations may occur even in the younger population under the age of 20 without any trauma or underlying disease. Favorable outcomes can be achieved by conventional treatments for cervical disc herniation.